Symbiosis in trepostome bryozoans from the Sandbian (Late Ordovician) of Estonia. (3rd June 2022) - Vinn, Olev; Ernst, Andrej; Wilson, Mark A.; Toom, Ursula
ABSTRACT: Anoigmaichnus bioclaustrations ( A. odinsholmensis, A. bretti, and A . isp.), unidentified large bioclaustrations, small conical bioclaustrations, cornulitids and conulariids occur in the Sandbian trepostome bryozoans of Estonia. The most abundant symbionts in the middle Sandbian bryozoans were Anoigmaichnus odinsholmensis bioclaustrations, making up about 72% of all bryozoan endobionts. The bryozoan Diplotrypa hosted the most diverse symbionts, and this Bryozoan genus was also among the most common trepostomes in the middle Sandbian of Estonia. Infestation of common bryozoans may have helped the endobiotic symbionts to survive and spread in the middle Sandbian. The taxonomic composition of the symbiotic endobiont fauna of the Sandbian of the Baltic Basin depended on the sedimentary facies. The lower Upper Ordovician boundary marks the beginning of a major regional increase in the diversity of bryozoan endobionts.